Zinc content in cord blood is associated with maternal age and parity - Youssof, Ayman Lee; Abu Kassim, Noor Lide; Rashid, Siti Aishah; Ley, Marc De; Rahman, Mohammad Tariqur (Humana Press Inc., 2017)
At childbirth (parturition), zinc (Zn) homeostasis in cord blood (CB) can be affected by a number of factors: Zn in maternal blood, parturition related stress as well as metallothionein (MT). Both Zn and stress are known inducers of MT which is primarily involved in Zn homeostasis. This study analyzed Zn concentration [Zn], in CB components and MT-2A transcription in CB mononuclear cells (MNC) in relation to primiparous and multiparous childbirth. [Zn] in CB (n = 47) plasma, erythrocytes, and MNCs were measured by atomic absorption spectrophotometry (λ = 213.9 nm). The MT-2A transcription in CB-MNC was quantified using real-time PCR. Significant correlations (Pearson r) were found between: plasma-[Zn] and erythrocyte-[Zn] (p = 0.002); [Zn] and MT-2A messenger RNA (mRNA) (p = 0.000) in CB-MNC. Student’s t tests showed higher levels of MT-2A mRNA and MNC-[Zn] in CB of older (≥25 years) compared to younger mothers (≤24 years) (p = 0.043 and p = 0.016, respectively). Significantly higher [Zn] was found in CB plasma (p = 0.017) and MNC (p = 0.041) of older primiparous compared to the younger primiparous and older multiparous mothers respectively. MT-2A mRNA in CB-MNC was significantly lower in CB of younger primiparous mothers compared to their older counterparts (p = 0.001). Path analysis showed that MNC-[Zn] (β = 0.83; p = 0.000) had a greater influence on MT-2A mRNA expression, compared to parity (β = −0.14; p = 0.033). Higher [Zn] in CB of primiparous mothers could be linked to higher stress during parturition, however, might be beneficial for the growth and development of the child. Together MNC-[Zn] and parity contributed ~70 % of the MT-2A transcription in CB-MNC.